ナンキョク コショウ ノ チキュウ カガク テキ トクチョウ - 綿抜, 邦彦; ワタヌキ, クニヒコ; 鳥居, 鉄也; トリイ, テツヤ; 村山, 治太; ムラヤマ, ハルタ; 平林, 順一; ヒラバヤシ, ジュンイチ; 佐野, 方昂; サノ, マサタカ; 我孫子, 勤; アビコ, ツトム; et al. (国立極地研究所, 1977)
P(論文) 南極オアシスの湖沼の多くは氷河,降雪の融氷水によって涵養されているが,大陸沿岸の塩湖には海水と同様の化学組成比を示す海跡湖がある.マクマードオアシスのような山岳オアシスの塩湖では,湖底堆積物および溶存塩類は海水起源であり,涵養水は氷河融氷水である.このような塩湖は地質時代を通じて蒸発乾固に近い状態になり,これが融氷水で抽出され現在の湖沼を形成したものと考えられる.海水より著しく塩分濃度の高い塩湖は,海水が低温下で濃縮されたものを源にしていると推定される.塩湖の硫化水素,栄養塩の分布,有機炭素の含有量,脂肪酸の含有量,メタン,窒素などの気体の存在は,塩湖における徴生物の活動を示唆するものであり,昭和オアシスの湖沼中の銅,亜鉛,鉛,カドミウムの存在度とその相対比から,これらの元素は降雪起源であり,人為的寄与も加わっている可能性が示された. Geochemical investigations of Antarctic lakes have been carried out on major components, nutrient matters, stable isotopes and organic substances in waters in order to clarify the geochemical features of the lakes. The present waters of inland lakes are supplied from the melt water of glacier or snow. But the waters of saline lakes on the coast of the continent have originated mainly from the sea water, for example Lake Nurume, Lake Hunazoko (Syowa Oasis) and Lake Fryxell (McMurdo Oasis). The isotopic compositions of waters in some lakes such as Lake Vanda, are similar to that of the snow or melt water of the glacier, while the isotopic composition of sulfur in the salt deposited or dissolved in the lake is similar to that of the sea origin sulfur compound. The water of highly saline lakes should have been produced in the process of concentration of the sea water under a frigid condition. For some of the lakes, it is considered that the water was evaporated once or several times and the residue were extracted with melt water of glacier. From the contents of organic substances, nutrient matters and gases in the lake, activity of microorganisms is suggested in some of the lakes. In view of the abundance and relative ratios of some heavy metal elements, such as copper, zinc, lead and cadmium, these elements should have been supplied from snow. departmental bulletin paper